Tributação, igualdade e livre concorrência: aspectos regulatórios da tributação no setor de cigarros - Gomes, Marcelo Batista Ludolf (2022)
The objective of this thesis is to investigate the relationship between equal taxation and free competition from the analysis of regulatory aspects of taxation in the cigarette sector. It begins with an analysis of the gradual and growing restrictive regulatory concept of the cigarette sector, notably under sanitary aspects, to arrive at the tax analysis, whether under the high tax burden, or even about the possibility of the tax authorities carrying out the termination of legal activity business of a society in the cigarette sector due to repeated tax default, without a political sanction, which is prohibited by the legal system. It goes on to analyze the concepts of a competitive nature and of an economic and financial order that support the aforementioned thesis of the State's closure of business activity in the tobacco sector. The dissertation aims to provide more than an exhaustive survey of the many legal aspects involved in sectoral regulation, but also a map of the multiple perspectives and constitutional values under discussion, which are often seen as apparently conflicting and, to a large extent, are still explored in depth by the literature and jurisprudence of the country.